HUBUNGAN ANTARA MOTIVASI DENGAN HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN PERSAMAAN DAN PERTIDAKSAMAAN LINIER SIWA KELAS X APK SMK YPM 3 TAMAN - Kartini Kartini (Universitas PGRI Adi Buana Surabaya, 2016)
This research is motivated by the fact of learning outcomes and a low level of mastery students were most likely caused by low motivation to learn is possessed by students. Motivation itself is based, the environment of the school and family environment. The design of this study used a correlational research design. This study aims to determine whether there is a relationship between motivation and learning outcomes on the subject of math equations and linear inequalities. Instrument of data collection using questionnaires to obtain data of motivation to learn, and test methods for obtaining data learning outcomes. The data were analyzed using correlation techniques poduct moment. The population in this study were students, the students of class X APK SMK YPM 3 Taman Sidoarjo were 112 students, while the sample is taken by random sampling as much as 35% of the 40 students. The research results obtained correlation coefficient = 0.379, later than at significant level of 5% and N = 40 is 0.312 Turns greater than . It can be concluded that there is a relationship between motivation and learning outcomes on the subject of math equations and linear inequalities. Keywords: learning motivation, learning outcomes, linear equations and inequalities